Intradural-Extramedullary Solitary Fibrous Tumor/Hemangiopericytoma with a Negative Result on Fluorodeoxyglucose-Positron Emission Tomography/Computed Tomography. (22nd November 2019) - Tomomatsu, Yusuke; Iizuka, Yoichi; Mieda, Tokue; Hirato, Junko; Koshi, Hiromi; Sonoda, Hiroyuki; Ishiwata, Sho; Kakuta, Yohei; Honda, Akira; Tajika, Tsuyoshi; Chikuda, Hirotaka
Abstract : Intradural-extramedullary solitary fibrous tumor/hemangiopericytoma (SFT/HPC) is a rare entity. SFT/HPCs can recur after surgery, even if a benign histology of the tumor is observed. We herein report a 68-year-old woman with intradural-extramedullary SFT/HPC. On magnetic resonance imaging (MRI), the intradural-extramedullary mass was isointense on T1-weighted images and hypointense on T2-weighted images with heterogeneous gadolinium enhancement. Whole-body fluorodeoxyglucose-positron emission tomography/computed tomography ( 18 F-FDG-PET/CT) was also performed, showing no accumulation. We performed surgery for the intradural-extramedullary mass, and the pathological findings of the resected specimen were a benign histology consistent with World Health Organization (WHO) grade I SFT/HPC. She had no evidence of tumor recurrence three years after the surgery for intradural-extramedullary SFT/HPC. 18 F-FDG-PET/CT before surgery may be useful for predicting the postoperative behavior of spinal SFT/HPCs.